Faktor Kejadian Balita Stunting Tahun 2022 - Faujannor, Akhmad; Nurzajuli, Nurzajuli; Suhartono, Suhartono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the factors that influence the incidence of stunting in toddlers in East Kotawaringin Regency, Central Kalimantan. The method used is a quantitative analytical survey with a cross-sectional study approach, and the data analysis used is the chi-square test. The research results show a relationship between family knowledge and the incidence of stunting with a value of p = 0.008. There is a relationship between exclusive breastfeeding and the incidence of stunting with a value of p = 0.005. There is a relationship between the birth weight of the baby and the incidence of stunting with a value of p = 0.000. There is a relationship between a history of diarrhea and the incidence of stunting with a p-value = 0.000. In conclusion, there is a relationship between family knowledge, exclusive breastfeeding, birth weight, and history of diarrheal disease and the incidence of stunting. Keywords: Exclusive Breastfeeding, Birth Weight, Family Knowledge, History of Diarrhea, Stunting